PENGARUH PEMBERIAN JUS BAYAM HIJAU TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER III DENGAN ANEMIA DI WILAYAH KERJA PUSKESMAS TANGGULANGIN - Yuni Yastutik, Iryani; Ratna Aminati, Fifi (PRIMA WIYATA HEALTH, 2022)
The prevalence of anemia according to Riskesdas (2018), in pregnant women in Indonesia is 48.9%. Although the government has implemented an anemia control program for pregnant women by giving 90 Fe tablets to pregnant women during the pregnancy period with the aim of reducing the anemia rate of pregnant women, the incidence of anemia is still high. Seeing the high incidence of anemia in pregnant women, one alternative that can be done to meet iron needs is by consuming vegetables that contain iron. One of them is spinach, especially green spinach. The aim of the study was to determine the effect of green spinach juice on the increase in hemoglobin levels of pregnant women in the third trimester with anemia. This type of research used in this study is a pre-experimental design with the form of one group pretest-postest design. The population in this study were all pregnant women in the working area of the Puguk Health Center, North Seluma District, which amounted to 135 pregnant women in 2020 with the sampling technique in this study was a total sample of 26 people, the statistical test used was the Paired sample T-statistical test. test. The results of this study indicate that, before pregnant women were given the intervention of green spinach juice, it was known that the average HB of anemia pregnant women was 8.608. After the intervention of green spinach juice, it is known that the average HB level of pregnant women is 13,546. There is an effect of giving green spinach juice on the increase in hemoglobin levels of pregnant women in trimester III with anemia. Suggestions are expected to the health center to increase participation in supporting pregnant women in carrying out treatment and how to prevent or treat anemia during pregnancy by increasing the mother's knowledge of how to treat and prevent anemia by utilizing plants and other alternatives that are cheap and easy to obtain.